The Political Economy of Bison Management in Wood Buffalo National Park - McCormack, Patricia A. (ARCTIC, 1992)
Nearly a century ago government initiatives saved Canada's wild bison from extinction, and in the 1920s Wood Buffalo National Park (WBNP) was established as a preserve for wood and plains bison. Today new government initiatives threaten these northern bison with extermination as a "game management" strategy. This paper outlines the history of bison management in WBNP and addresses critical issues for the 1990s. It is argued that until the mid-1960s, when the park came under the jurisdiction of Parks Canada, management strategies were presented as biologically based but were conditioned by external political and economic considerations. Similarly, an analysis of current proposals to "replace" the bison of WBNP concludes the contemporary issues of political economy are obscured by attempts to justify the plan on biological grounds.Key words: bison, game management, Wood Buffalo National Park, political economy, EARP, tuberculosis, brucellosis RÉSUMÉ. Il y a presque un siècle, des mesures instaurées par le gouvernement ont empêché la disparition du bison sauvage canadien et, durant les années 20, le parc national Wood Buffalo a été créé en tant que réserve intégrale pour le bison des bois et le bison des plaines. Aujourd’hui, de nouvelles mesures prises par le gouvernement dans le cadre d’une stratégie d’aménagement cynégétique menacent ces bisons du Nord de disparition complète. Cet article retrace l’historique de la conservation du bison dans le parc national Wood Buffalo et traite des enjeux critiques des années 90. Il soutient que, jusqu’au milieu des années 60, lorsque le parc a commencé à faire partie de Parcs Canada, les stratégies de conservation étaient mises de l’avant sur des bases biologiques mais qu’elles étaient en fait conditionnées par des considérations politiques et économique. De la même façon, une analyse des propositions actuelles visant à remplacer le bison du parc national Wood Buffalo nous amène à conclure que les enjeux actuels d’économie politiques ont brouillés par la tentative de ...